5
$\begingroup$

Lie bracket of vector fields is defined in two ways:

Let $\Phi^X_t$ be the flow associated with the vector field $X$, and let $d$ denote the tangent map derivative operator. Then the Lie bracket of $X$ and $Y$ at the point $x \in M$ can be defined as $[X, Y]_x := \lim_{t \to 0}\frac{(\mathrm{d}\Phi^X_{-t}) Y_{\Phi^X_t(x)} - Y_x}t = \left.\frac{\mathrm{d}}{\mathrm{d} t}\right|_{t=0} (\mathrm{d}\Phi^X_{-t}) Y_{\Phi^X_t(x)}$

or equivalently $[X, Y]_x := \left.\frac12\frac{\mathrm{d}^2}{\mathrm{dt}^2}\right|_{t=0} (\Phi^Y_{-t} \circ \Phi^X_{-t} \circ \Phi^Y_{t} \circ \Phi^X_{t})(x) = \left.\frac{\mathrm{d}}{\mathrm{d} t}\right|_{t=0} (\Phi^Y_{-\sqrt{t}} \circ \Phi^X_{-\sqrt{t}} \circ \Phi^Y_{\sqrt{t}} \circ \Phi^X_{\sqrt{t}})(x)$

How does one show by math that these two definitions are equivalent? And for the second definition, how does one show that $\left.\frac12\frac{\mathrm{d}^2}{\mathrm{dt}^2}\right|_{t=0} (\Phi^Y_{-t} \circ \Phi^X_{-t} \circ \Phi^Y_{t} \circ \Phi^X_{t})(x) = \left.\frac{\mathrm{d}}{\mathrm{d} t}\right|_{t=0} (\Phi^Y_{-\sqrt{t}} \circ \Phi^X_{-\sqrt{t}} \circ \Phi^Y_{\sqrt{t}} \circ \Phi^X_{\sqrt{t}})(x)$?

$\endgroup$
1
$\begingroup$

Let $c(t)= \psi_{-t} \circ \phi_{-t} \circ \psi_t \circ \phi_t(p)$. In his book A comprehensive introduction to differential geometry, Spivak shows that $c'(0)=0$ and $c''(0)=2[X,Y]_p$ (Prop. 15 and Thm. 16, p. 160-163).

To simplify the notations, he defines $$\begin{array}{l} \alpha_1(t,h)= \psi_t \circ \phi_h(p) \\ \alpha_2(t,h)=\phi_{-t} \circ \psi_h \circ \phi_h(p) \\ \alpha_3(t,h) = \psi_{-t} \circ \phi_{-h} \circ \psi_h \circ \phi_h(p) \end{array}$$ so that $c(t)= \alpha_3(t,t)$. Noticing that $$\begin{array}{l} \alpha_2(0,t)= \alpha_1(t,t) \\ \alpha_3(0,t)= \alpha_2(t,t) \end{array}$$ and for any $f \in C^{\infty}(M)$ $$\begin{array}{ll} \partial_t(f \circ \alpha_1) = Yf \circ \alpha_1 & \partial_t(f \circ \alpha_2)=-Xf \circ \alpha_2 \\ \partial_t(f \circ \alpha_3)=-Yf \circ \alpha_3 & \partial_h(f \circ \alpha_1)(0,h)=Xf(\alpha_1(0,h)) \end{array}$$ the identities $c'(0)=0$ and $c''(0)=2[X,Y]_p$ are shown using differential calculus.

Then, the identity $[X,Y]_p = \frac{d}{dt}_{|t=0} \psi_{-\sqrt{t}} \circ \phi_{-\sqrt{t}} \circ \psi_{\sqrt{t}} \circ \phi_{\sqrt{t}}(p)$ can be deduced from the previous one using the following lemma (Ex. 16, p. 176):

Lemma: Let $c : \mathbb{R} \to M$ be a smooth curve satisfying $c'(0)=0$. If $\gamma(t)=c(\sqrt{t})$, then $$\lim\limits_{h \to 0^+} \frac{\gamma(h)- \gamma(0)}{h}= \frac{1}{2}c''(0)$$

In fact, because we only consider $f \circ c$ where $f \in C^{\infty}(M)$, it is sufficient to show the lemma for $c : \mathbb{R} \to \mathbb{R}$. But $$c(h)=c(0)+ \underset{=0}{\underbrace{c'(0)}} \cdot h+ \frac{1}{2}c''(0) \cdot h^2+o(h^2)$$ implies $$\frac{c(\sqrt{h})-c(0)}{h}= \frac{1}{2}c''(0)+o(1).$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.